2022
DOI: 10.1177/15589447221130092
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Endoscopic Carpal Tunnel Release: A Comparison of Opioid Prescription Patterns and Occupational Therapy Referrals

Abstract: Background: Endoscopic and open carpal tunnel releases (ECTR and OCTR) are safe and effective operations. We compared the approaches in terms of postoperative opioid refills and occupational therapy (OT) referrals. Methods: We conducted a retrospective study of patients with carpal tunnel syndrome (CTS) treated with ECTR or OCTR. Patients with isolated idiopathic CTS were included; patients undergoing simultaneous bilateral carpal tunnel release (CTR), revision CTR, and additional procedures at time of CTR wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Four cases experienced the need for re-operation in the ECTR group, and three events of re-operation were noticed in the OCTR group [ 26 ]. As pain is one of the postoperative outcomes, a study conducted by Schroeder et al in 2022 on 1,125 patients with CTS who underwent open and endoscopic surgery found that postoperative opioid use was similar in both groups [ 32 ]. In a study conducted by Liawrungrueang et al in 2022, they found a decrease in short-term pain in the ECTR in a follow-up period extended to two weeks [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Four cases experienced the need for re-operation in the ECTR group, and three events of re-operation were noticed in the OCTR group [ 26 ]. As pain is one of the postoperative outcomes, a study conducted by Schroeder et al in 2022 on 1,125 patients with CTS who underwent open and endoscopic surgery found that postoperative opioid use was similar in both groups [ 32 ]. In a study conducted by Liawrungrueang et al in 2022, they found a decrease in short-term pain in the ECTR in a follow-up period extended to two weeks [ 33 ].…”
Section: Reviewmentioning
confidence: 99%